Even climate change is not fair: the impact of climate change on economic outcomes - Vincent Tawiah; Noha Alessa (International Journal of Climate Change Strategies and Management, 2024)
Purpose – From generation to generation, the poor and less developed have always borne the negative consequences of the extravagant lifestyles of the rich. The climate seems to perpetuate this injustice by punishing the good people with the consequences of the irresponsible acts of the wealthy. Therefore, this paper aims to establish the relationship between climate risk and carbon emissions. Then, this paper investigates the economic consequences of climate risk in both developed and developing countries. Design/methodology/approach – This paper uses robust econometrics, including fixed effect and the two-step system generalised method of moments, on a large sample of 175 countries from 2008 to 2019. Findings – Unsurprisingly, this paper found that climate risks are negatively associated with carbon emissions, indicating that countries with lower emissions are more exposed to frequent and severe climate-related disasters than those with higher emissions. Additionally, this paper discovered that climate risk has a negative impact on economic development, which is more pronounced in developing countries. The results are robust to alternative measurement and econometric modelling, including the system-generalized method of moments. Originality/value – These findings suggest that developing countries, the least contributors to climate change, unfairly suffer from the environmentally irresponsible actions of high-emitting developed countries.